Wirtschaftliche Konvergenz trotz politischer Unsicherheit; Economic convergence despite political uncertainty - Julia Grübler (The Vienna Institute for International Economic Studies (wiiw), 2017)
Das internationale Umfeld für die Wirtschaft der mittel-, ost- und südosteuropäischen Länder (MOSOEL) präsentiert sich als Kontrast zwischen wirtschaftlichem Aufschwung einerseits sowie politischer Unsicherheit und geopolitischen Spannungen andererseits. Kurzfristig setzen sich die positiven Effekte der wirtschaftlichen Erholung im Euroraum und der damit verbundenen Exporte, sowie des relativ niedrigen Ölpreises gegen mögliche negative Effekte politischer Turbulenzen durch. Gegenüber der wiiw-Frühjahrsprognose wurden die Wachstumsprognosen für die MOSOEL größtenteils nach oben auf 2,4% für das laufende Jahr und 2,6% für das Jahr 2018 korrigiert. – – The international environment for the economies in Central, East and Southeast Europe (CESEE) is characterised by a contrast between economic upswing, on the one hand, and political uncertainty and geopolitical tensions, on the other hand. In the short term, positive effects of the economic recovery in the euro area and related exports, as well as of the relatively low oil price are prevailing over potential negative effects of political turmoil. Compared with the wiiw Spring Forecast, growth projections for the CESEE region were for the most part revised upwards, to 2.4% and 2.6% for the years 2017 and 2018, respectively.
Keywords: E20; E66; O52; O57; P24; P27; P33; P52; 330; Konjunkturprognose; Mittelosteuropa; Westbalkan; Österreich; MOSOEL; Internationaler Handel; Investitionen; Migration; Economic Forecast; Central and Eastern Europe; Western Balkans; Austria; CESEE; International Trade; Investment; Migration